China's Investment in Bangladesh: Backdrop of Debt Trap Diplomacy - Rahman, Md.Mizanur (International Journal of Applied Research and Sustainable Sciences, 2024)
This research investigates the implications of Chinese investment in Bangladesh, particularly in the context of concerns surrounding debt trap diplomacy. As China extends its Belt and Road Initiative (BRI), Bangladesh has emerged as a significant recipient of Chinese loans and investments, encompassing infrastructure projects such as ports, power plants, and highways. While these investments are poised to bolster Bangladesh's economic development, they also raise concerns about the potential for unsustainable debt levels and the erosion of sovereignty. This study delves into the economic, political, and social ramifications of Chinese investments in Bangladesh. Through a mixed-methods approach combining quantitative analysis of debt sustainability indicators and qualitative assessments from stakeholder interviews, the research examines whether Chinese funding is leading to a debt trap scenario. Preliminary findings suggest that while Chinese investments have accelerated infrastructure development, they have also increased Bangladesh's debt burden and dependency on China. Furthermore, the strategic placement of investments suggests potential geopolitical motivations behind Chinese funding. This research aims to contribute to the broader discourse on the impact of Chinese foreign direct investment in developing countries, offering policy recommendations for Bangladesh to navigate the complexities of foreign financing without compromising its economic sovereignty. The study underscores the necessity for rigorous debt management and transparent investment policies to mitigate the risks associated with large-scale foreign loans.